Dietary knowledge-attitude-practice status in hemodialysis patients: a latent profile analysis - Zhiqian Chen; Na Xu; Xinxin Chen; Xiaoyu Zhang; Shuqing Yin; Guanghui Xiao; Li Luo; Qun Liu; Chunyan Su (BMC, 2024)
Abstract Background Hemodialysis patients require a reasonable dietary intake to manage their disease progression effectively. However, there is limited research on these patients' overall dietary knowledge, attitude, and practice (KAP) status. This study aimed to investigate the dietary KAP status and latent profiles in hemodialysis patients and identify sociodemographic and disease-related factors associated with these profiles and dietary practice. Methods A multicenter cross-sectional study involving 425 hemodialysis patients was conducted. A dietary KAP questionnaire in hemodialysis patients was used to evaluate the dietary KAP of the patients. A structural equation model was employed to analyze the correlations between dietary knowledge, attitude, and practice. Multiple linear regression analysis was used to identify factors associated with dietary practice scores. Latent profile analysis was conducted to determine the latent profiles of dietary KAP, and binary logistic regression was used to explore the sociodemographic and disease-related characteristics associated with each KAP profile in hemodialysis patients. Results The normalized average scores for dietary knowledge, attitude, and practice in hemodialysis patients were 0.58, 0.82, and 0.58, respectively. The structural equation model revealed significant positive correlations between dietary knowledge and attitude, and attitude and practice. Attitude played an indirect effect between knowledge and practice. Gender, cerebrovascular disease, and dietary attitude scores were identified as independent influencing factors for dietary practice scores. Two dietary KAP profiles were developed: a profile with general knowledge and attitude but low practice (40.2%) and a profile with general knowledge and attitude and high practice (59.8%). Binary logistic regression analysis indicated gender and monthly income per household significantly predicted membership in each KAP profile. Conclusions The dietary practice of hemodialysis patients requires improvement. It is necessary to develop more individualized dietary interventions for these patients. Further exploration is needed to understand the motivation of patients to change their dietary behavior.